PERILAKU BERWISATA PENDUDUK SUMATERA BARAT DITINJAU DARI FAKTOR SOSIAL EKONOMI - Astuti, Dewi (Jurnal Pariwisata Pesona, 2019)
The West Sumatra tourism sector has the potential to be developed. Increasing tourism supporting infrastructure continues. The characteristics of the residents who are traveling need to be a concern to determine the direction of policy in the tourism sector. This study aims to look at the influence of socio-economic characteristics to the decision of residents who are traveling in West Sumatra. The data used is the 2017 Indonesian Socio Economic Survey data. The method used is the Binary Logistic Regression Model. Binary logistic regression is a method of data analysis to find the relationship of dependent variables that only consist of two categories. The results of this study explained that the decision of the resident of West Sumatra to travel was significantly influenced(Î±=5%) by socio-economic factors of age, age, sex, education, marital status, family status, and residence.